The impact of emotional intelligence on operational effectiveness: The mediating role of organizational citizenship behavior and leadership (2023)
This article examines the influence of emotional intelligence on organizational citizenship behavior and transformational and transactional leadership, and the impact of these dimensions on operational effectiveness.